Pengaruh Aplikasi Duolingo terhadap Keterampilan Membaca Bahasa Jerman Siswa Kelas XI SMA Swasta Kampus Nommensen Pematangsiantar: The Influence of Duolingo Application on German Reading Skills of Grade XI Students of Nommensen Campus Private High School, Pematangsiantar - Simanjuntak, Tarida Alvina; Situmorang, Stephany Angelia; Silalahi, Rina Elnica (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to determine the effect of the Duolingo application on German reading skills of class XI SMA Swab Nommensen Campus Pematangsiantar. The type of this research is an Experimental study with the Pre Experimental type using the One Group Pretest-Posttest design. The population in this study were students of class XI SMA Swab Nommensen Campus Pematangsiantar with a sample of 39 people. Sampling using Cluster Sampling and data collection techniques through test techniques obtained from multiple choice questions. The use of Duolingo in this study went through the pretest and posttest stages. Based on the results of data analysis and the results of the hypotheses tested in this study, it can be seen that there is an effect on students' reading skills before and after the Duolingo application was implemented. The results of the student test assessment on the pretest or before the implementation of the learning media reached an average of 45.78 in the less category. The results of the student test assessment on the posttest or after the implementation of the Duolingo application increased to 87.79 in the good category. Therefore, based on the results of the pretest and posttest, there is a difference in the results of the reading skills of class XI students of SMA Swasta Kampus Nommensen Pematangsiantar before and after implementing the Duolingo application. Based on the analysis of student reading skills data in the pretest and posttest, tcount = 12.01 was obtained at a significance level of 0.05 (95% confidence level) at df = 38, ttable = 1.686 was obtained. Then tcount = 12.01> tcount = 1.686, so it can be concluded that H0 is rejected and Ha is accepted, so there is a significant influence between before and after implementing the Duolingo application.